Estimating the adoption of modern cultivars in Rajasthan: A descriptive analysis - Varshney, Deepak; Joshi, Pramod Kumar; Roy, Devesh (International Food Policy Research Institute, 2019)
One of the most promising strategies to boost farmers’ income in developing countries is the adoption of improved technologies, such as modern cultivars that may produce higher yields. This study aims to examine the adoption of modern cultivars in Rajasthan, one of India’s northern states. Our analysis is based on a primary survey of 1,500 farmers covering four major crops: wheat, mustard, pearl millet, and gram. The study aims to identify the farmer-level constraints in adopting modern cultivars and decomposing into the elasticity of adoption probability and the use intensity. The study also attempts to assess the role of the key characteristics of cultivars in their adoption. The authors implemented McDonald and Moffitt’s (1980) approach to decompose the overall elasticity into the elasticity of adoption probability and use intensity. To present cultivar-specific analysis, the authors modeled farmers’ decisions to adopt top cultivars accounting for concerns regarding independence of irrelevant alternative assumption in a multinomial logistics framework.